Kualitas Layanan Last-Mile Delivery: Studi Komparasi Dua Layanan Pesan-Antar Makanan - Iwan Setyawan; Rudi Laksono; Junias Robert Gultom (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Last-mile delivery (LMD) plays an important role in meeting the needs of online food delivery. The LMD industry, such as Gojek with GoFood services and Grab with GrabFood services, provides pick-up services for orders from merchants and delivers them to the customer. In the online ordering process, the courier acts as a merchant representative, so whether or not the service provided by the courier will have an impact on the merchant. The purpose of this study is to determine the differences in the quality of services provided by GoFood and GrabFood. This research uses a quantitative approach. The population in this study were GoFood and GrabFood customers in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. The sample was selected using simple random sampling. Data analysis used Multivariate Analysis of Variance (MANOVA). The study found differences in the quality of last-mile delivery services between GoFood and GrabFood. The difference lies in the dimensions of responsiveness, assurance, empathy, and physical evidence, while for the reliability dimension, the two services are not different or the same.